Towards better management of the Indian public sector (New Delhi, 1982)
The Documentation Centre which came into existence in September, 1978 and started its active carrer from March, 1979, has during the short period of three years, diversified its activities in the directions of bringing out publications for reference use by the executives in the public and private sectors, running several periodic feature services for the professionals and managerial personnel connected with corporate undertakings, organising workshops, seminars and short-term courses on corporate management and finiancial disciplines and holding several annual lectures on subjects relevant to the trade and industry and of national importance.
Keywords: Govt. business enterprises